Influence Social Media Marketing and Marketing Mix of Repurchase Decision Mediated By Repurchase Intention - Silalahi, Nirawaty; Heryjanto, Andreas (CV. Publikasi Indonesia, 2023)
The purpose of this study was to determine the effect of social media marketing and marketing mix on repurchase decisions mediated by repurchase intention among consumers of Paramount Land Gading Serpong Tangerang. This is a type of quantitative research with the research population being consumers who have purchased and owned property at PT Paramount Land. The sampling technique in this research is non-probability sampling with purposive sampling. The sample used for respondents in this study amounted to 173 respondents. Based on Hair et al that the minimum sample size is 5-10 times the number of indicators and the author uses 5 times the indicator. The data analysis technique used descriptive analysis of Partial Least Square Structural Equation Modeling (PLS-SEM) to measure the relationship between variables with the help of Smart PLS software. The research results indicate that social media marketing has a significant positive influence on repurchase decision, marketing mix has a significant positive influence on repurchase decision, social media marketing has a significant positive influence on repurchase intention, marketing mix has a significant positive influence on repurchase intention, repurchase decision has a significant positive influence on repurchase intention, social media marketing has a significant positive influence on repurchase decision mediated by repurchase intention, marketing mix has a significant positive influence on repurchase decision mediated by repurchase intention